2021
DOI: 10.3389/fonc.2021.705927
|View full text |Cite|
|
Sign up to set email alerts
|

Results of the ECHO (Eating habits CHanges in Oncologic patients) Survey: An Italian Cross-Sectional Multicentric Study to Explore Dietary Changes and Dietary Supplement Use, in Breast Cancer Survivors

Abstract: The role of a healthy diet in cancer prevention is well recognized. Recent data indicate that following the same advices can also improve cancer survivors’ quality of life. Breast cancer (BC) patients are commonly concerned about diet and nutrition and frequently express the need to obtain health-related information and the will to change their diet and lifestyle. Hence, be aware of survivors’ dietary changes and information needs is crucial for healthcare professionals to guide them toward optimal lifestyle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The effect of yoghurt may be mediated by microbiota modification in a healthier direction. This is consistently described for yoghurt, with less evidence for other dairy products [36], partially explaining why results for other dairy products-mainly the nonfermented ones-are less consistent [27], thus resulting in the categorization of dairy products into specific food groups [37].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The effect of yoghurt may be mediated by microbiota modification in a healthier direction. This is consistently described for yoghurt, with less evidence for other dairy products [36], partially explaining why results for other dairy products-mainly the nonfermented ones-are less consistent [27], thus resulting in the categorization of dairy products into specific food groups [37].…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, different compositions of gut microbiota have been described in relation to different CRC types and outcomes [25,26]. Our data refer to the year before CRC diagnosis/interview, used as a proxy for usual diet of the participants who could have changed their habits once aware of the disease or because of symptoms [27].…”
Section: Discussionmentioning
confidence: 99%
“…Question 2: Clinical interpretation. Although interest in dietary modification for the purpose of improving cancer outcomes or reducing treatment toxicity remains high, [103][104][105] there are very few data at this time to support specific dietary modifications or foods as a part of cancer treatment. Neutropenic diets, generally defined as diets that seek to reduce bacterial exposure by limiting raw fruits and vegetables, have long been recommended to prevent infection in patients with hematologic malignancies, and especially in individuals who have undergone bone marrow transplant.…”
Section: Literature Review and Analysismentioning
confidence: 99%
“…Our study identified factors associated with the likelihood of attention to lifestyle factors as part of oncology care, including time since diagnosis, current treatment status, race and ethnicity, cancer type, and BMI. The finding that patients with breast cancer were more likely to receive advice regarding exercise and weight management likely reflects both the significant body of research supporting the role of these factors in breast cancer outcomes and patients with breast cancer's high level of interest in these topics 22,23,24 . The increased attention to diet, exercise, and weight during oncology visits in patients diagnosed with cancer more recently suggests that the development of guidelines providing recommendations for a healthy lifestyle after cancer diagnosis may have increased awareness of these topics in oncology providers and patients.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that patients with breast cancer were more likely to receive advice regarding exercise and weight management likely reflects both the significant body of research supporting the role of these factors in breast cancer outcomes and patients with breast cancer's high level of interest in these topics. 22,23,24 The increased attention to diet, exercise, and weight during oncology visits in patients diagnosed with cancer more recently suggests that the development of guidelines providing recommendations for a healthy lifestyle after cancer diagnosis may have increased awareness of these topics in oncology providers and patients. Notably, despite the attention to diet, exercise, and weight as a part of their oncology care, more than 50% of survey respondents were overweight/had obesity and reported infrequent exercise and low rates of fruit and vegetable intake.…”
Section: Discussionmentioning
confidence: 99%